Antioxidant (Oxiprovin TM) supplementation and muscle recovery from contusion injury - an in vivo study - Kruger, Maria Jacoba (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.